Product characteristics and kinetics of sewage sludge pyrolysis driven by alkaline earth metals - S. Tang; Zheng, C.; Yan, F.; Shao, N.; Y. Tang; Z. Zhang (Energy, 2018)
Alkaline earth metals (AEMs) aggregated in sludge minerals influence the pyrolysis characteristics and product distribution. Sewage sludge pyrolysis behaviors driven by AEMs were first investigated using advanced thermogravimetry sequentially combined with Fourier transform infrared spectroscopy and mass spectrometry (TG-FTIR-MS). The AEMs represented by MgO and CaO affected the release of volatile products in different ways during sludge pyrolysis. Over 440 °C, CaO and MgO additions both enhanced total absorbance of pyrolytic volatiles, while the enhancement coming from CaO was stronger. Both additions reduced the release order of alkanes and olefins by varying degrees. The degree of reduction with MgO was more significant than that with CaO, while CaO addition promoted the release of CH4, C4H8 and C5H10 over 490 °C with respect to MgO. The addition of MgO more severely suppressed the release of pollutants including NH3, HCN, NO2, H2S, CH3SH, COS, SO2 and nitrogen-derived aromatics than that of CaO. The catalytic effect induced by both species was evidenced by the related pyrolysis kinetics. The attained results revealed that AEM-containing minerals are promising candidates for pollution control during sludge pyrolysis for value-added products recovery. © 2018 Elsevier Ltd